Awareness Regarding Primary Eye Care Among Primary Healthcare Workers of Pakistan: a Way to Revitalize Health for All! http://doi.org/10.36351/pjo.v37i2.1146 - Rehman, Noor ur; Sharif, Hina (Pakistan Journal of Ophthalmology, 2021)
Purpose: To assess awareness regarding Primary Eye Care among (primary healthcare workers) PHCWs and also intended to identify its determinants. Study Design: Descriptive cross-sectional study. Place and Duration of Study: All primary healthcare facilities of Tehsil Kallar Syedan, from October 2019 to December 2019. Methods: The calculated sample size was 115. Data was collected from primary health care workers (PHCWs). Data was collected through a structured questionnaire with both open-ended and close-ended questions. Questions were made using simple language and were also translated in Urdu. Questionnaire was adapted from two articles and some questions were made after reading the components of National Programme for Prevention and Control of Blindness (Punjab, Pakistan).Chi-square test of independence was used for finding associations. Results: Fifty-four percent PHCWs had poor awareness regarding primary eye care. Majority of the PHCWs, N = 64 (55.7%) identified just the names of common eye diseases. Cataract was identified with correct treatment by 88% primary healthcare workers. Age, education, designation were significantly associated with awareness of PHCWs. Conclusion: The study concluded that more than half of PHCWs had low awareness regarding PEC. All of them mentioned that there was a need of improving and refreshing their knowledge related to primary eye care. This will definitely help to reduce pressure on secondary and tertiary healthcare workers. Key Words: Primary eye care, Primary healthcare workers, Primary healthcare facilities, Pakistan.